2019
DOI: 10.1111/mcn.12835
|View full text |Cite
|
Sign up to set email alerts
|

Stunting trajectories from post‐infancy to adolescence in Ethiopia, India, Peru, and Vietnam

Abstract: Many interventions focus on preventing stunting in the first 1,000 days of life. We take a broader perspective on childhood growth to assess the proportions of children who suffer persistent stunting, recover, and falter and become newly stunted between birth and adolescence. We use longitudinal data collected on 7,128 children in Ethiopia, India, Peru, and Vietnam. Data were collected in five survey waves between the ages of 1 to 15 years. We use descriptive and graphical approaches to compare the trajectorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
0
20
2
Order By: Relevance
“…The results of present study highlight the importance of choice of references used to estimate the height status of children and adolescents to determine stunting, as it can signi cantly impact the strategies implemented by policy makers to address this abnormality. An appropriate assessment of stunting can also affect the decision of paediatricians to treat such a condition as now there is growing evidence that catch-up growth is possible till 15 years of age (14), thereby children can be stunted during early adolescence and can recover also by the use of timely strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of present study highlight the importance of choice of references used to estimate the height status of children and adolescents to determine stunting, as it can signi cantly impact the strategies implemented by policy makers to address this abnormality. An appropriate assessment of stunting can also affect the decision of paediatricians to treat such a condition as now there is growing evidence that catch-up growth is possible till 15 years of age (14), thereby children can be stunted during early adolescence and can recover also by the use of timely strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches in different populations provide growing body of evidence that there is a potential of catch-up growth in adolescent age among children with stunting. This catch-up linear growth can possibly lead to transition from stunted to non-stunted state during a growth phase known as the window period (14,15). The chances of catch-up growth are increased by adequate hygiene and nutrition, since children continuing to live in poorer/inadequate environments have limited potential for catch-up growth (16).…”
Section: Introductionmentioning
confidence: 99%
“…While the relevance of nutrition-specific interventions during the first two years of life cannot be contested, evidence on reversible nature of growth failures at later ages should also be emphasized. For example, a recent study analyzing longitudinal data from multiple LMICs found that children are both at risk of becoming stunted and potentially recovering post two years of age [9]. Randomized control trials (RCT) have claimed that improvements in the living environment and overall socioeconomic well-being can significantly improve anthropometric outcomes irrespective of children's age [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This is a key concern for researchers as well as policymakers. Studies based on longitudinal data suggest that children can become stunted or recover from stunting during birth to adolescence [9] and therefore, this limitation does not affect inferences made in this study. Third, the wealth index provided by NFHS was taken as a proxy for household income; therefore, any conclusion regarding poverty and deprivation can be sensitive to the adopted proxy for household economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation